THE IMPACT THAT SOCIAL MEDIA HAS HAD ON TODAY'S GENERATION OF INDIAN YOUTH: AN ANALYTICAL STUDY - Showkat Dar; Dolly Nagrath (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Social media has become a daily habit in most people’s lives. People of all ages participate in social media, and the average Indian devotes nearly 2.4 hours per day to this one activity alone. People are able to voice their concerns and share their perspectives through the medium of social media. When it comes to understanding social media, people must first be comfortable with the notion. Users can communicate with one another and share information, thoughts, opinions, images, and videos via Internet-based programmes known as "social media.. In order to access content, share content with other users of that social media platform, and converse with other users of that social media platform, an individual must first sign up for an account and then sign in to that account. Facebook, Twitter, WhatsApp, Snap Chat, Telegram, and LinkedIn are just a few of the most prominent and frequently used social networking platforms today; others include Snap chat etc. It's noteworthy to observe that most of these social networking sites have a disproportionately high proportion of teen users. In India, adolescents and teenagers between the ages of 13 and 19 make up 31 percent of the overall number of people who use social media (Statista, 2021). Users in India between the ages of 18 and 24 make up the majority of Facebook and Instagram users in the country. We take a descriptive and analytical stance when discussing social media and its effects on young people, both good and bad, in this study. We heavily rely on the thematic analysis tool MAXQDA to draw a conclusion. We discuss all facets of social media, including both positive and bad effects. Specific areas including business, education, society, and young people are highlighted.